2012
DOI: 10.1200/jco.2011.37.4546
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Trastuzumab in Combination With Cytotoxic Chemotherapy for Treatment of Metastatic Osteosarcoma With Human Epidermal Growth Factor Receptor 2 Overexpression: A Report From the Children's Oncology Group

Abstract: A B S T R A C T PurposeDespite efforts to intensify chemotherapy, survival for patients with metastatic osteosarcoma remains poor. Overexpression of human epidermal growth factor receptor 2 (HER2) in osteosarcoma has been shown to predict poor therapeutic response and decreased survival. This study tests the safety and feasibility of delivering biologically targeted therapy by combining trastuzumab with standard chemotherapy in patients with metastatic osteosarcoma and HER2 overexpression. Patients and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
168
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 206 publications
(173 citation statements)
references
References 38 publications
(8 reference statements)
2
168
0
3
Order By: Relevance
“…IgG antibodies constitute one of the most important host adaptive immune mechanisms and bridge the interactions between innate immunity such as mediated by NK and phagocytic macrophages with adaptive cellular immunity mediated by T cells (18,19,22). It is well documented that the Fc regions of IgGs play key roles in eliminating target cells, and Fc-mediated effector functions have been shown to contribute to the efficacy of several cancer therapeutic monoclonal antibodies (30)(31)(32). Our recent studies demonstrated that single-strand hinge cleavage of the anti-HER2 IgG1 antibody trastuzumab impaired its antitumor efficacy due to the loss of Fc-mediated effector functions (6,10).…”
Section: Discussionmentioning
confidence: 99%
“…IgG antibodies constitute one of the most important host adaptive immune mechanisms and bridge the interactions between innate immunity such as mediated by NK and phagocytic macrophages with adaptive cellular immunity mediated by T cells (18,19,22). It is well documented that the Fc regions of IgGs play key roles in eliminating target cells, and Fc-mediated effector functions have been shown to contribute to the efficacy of several cancer therapeutic monoclonal antibodies (30)(31)(32). Our recent studies demonstrated that single-strand hinge cleavage of the anti-HER2 IgG1 antibody trastuzumab impaired its antitumor efficacy due to the loss of Fc-mediated effector functions (6,10).…”
Section: Discussionmentioning
confidence: 99%
“…All patients received methotrexate, doxorubicin, and cisplatin, with the possible addition of ifosfamide or trastuzumab. [41][42][43] Patient outcome data through June 2012 were obtained from the COG. A single patient with metastatic disease at initial presentation had only completed 3.4 y of off-treatment follow up.…”
Section: Methodsmentioning
confidence: 99%
“…However, no statistical difference was found between the study arm and the standard arm 41 . There is a clear need for newer effective agents for patients with osteosarcoma.…”
Section: Chaptermentioning
confidence: 62%